Seroprevalence of acute hepatitis C virus infection among mortuary workers and ambulance drivers in Plateau State, Nigeria - Jeremiah M Uruku; Amos Dangana; Idris-Abdullahi Nasir; Bibiana N Egenti; Nimzing Lohya; Enenche S Iyalla; Kadiri Ezra; Emmanuel O Falade (SpringerOpen, 2018)
Nigeria is one of the countries highly endemic for viral hepatitis. However, data on the prevalence of hepatitis C virus (HCV) infection among mortuary workers and ambulance drivers has not been documented. Hence, this study sought to determine the seroprevalence of HCV among mortuary workers and ambulance drivers in Plateau State, North Central Nigeria. Between December 2015 and February 2016, a total of 80 blood samples were collected from mortuary workers and ambulance drivers with the view to test for HCV antibody using rapid immunochromatographic test (ICT) and enzyme-linked immunosorbent assay for anti-HCV immunoglobulin M. Three milliliter of blood was collected from each patient and the serum was separated out and used for the screening. A self-administered questionnaire was used to access the patients' sociodemographic variables. Of the 80 samples analyzed, five (6.3%) were positive for HCV using the rapid immunochromatographic assay, while two (2.5%) were positive for anti-HCV immunoglobulin M. There was no statistical association between seroprevalence of HCV with age and sex of patients. However, the seroprevalence of HCV was significantly associated with contact with blood, number of sexual partners, use of gloves, and history of sexually transmitted infections (P<0.05). The HCV seroprevalence of 2.5% among mortuary workers and ambulance drivers was relatively low; however, this suggests that the patients are at-risk group for occupational infection due to HCV.